(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Background: Cervical spondylotic myelopathy is associated with pathological changes in the spinal cord which is often reflected by the change in the signal intensity of the spinal cord observed on Magnetic Resonance Imaging (MRI). The prognostic significance of this signal intensity changes in preoperative patients remains controversial. Objectives: To compare the recovery rate on the 30th postoperative day, between the cervical spondylotic myelopathy patients with and without preoperative hyperintensity changes in the cervical cord in MRI T2 weighted images. Materials and Methods: The type of the study was surgical prospective study. The place of the study was Bangladesh Medical University, Dhaka. The study population consisted of cervical spondylotic myelopathy patients of all ages and both sexes. Only the patients with a single level disc prolapse were included. All patients underwent anterior cervical discectomy and fusion (ACDF) with titanium cage. Purposive sampling was used as the sampling technique. Sample size was 32. Interviewer administered questionnaires and data collection sheets were used as data collection tools. There was no loss to follow up patients. Statistical analysis: Data were processed and analyzed by using computer software SPSS (Statistical Package for Social Sciences) version 26. Unpaired t test, Fisher’s exact test and Mann-Whitney U test were done for data analysis. Statistical significance was set at p-value <0.05. Results: In this study, the patients were divided into Group A and Group B based on the presence or absence of hyperintensity changes in T2 weighted MRI images.There was a statistically significant difference between groups A and B regarding the recovery rate of the patients (p-value 0.043). The median recovery rate of Group A and Group B were 33% and 75% respectively. Fifteen (93.8%) and thirteen (81.3%) patients were male in Group A and Group B respectively. Eight (47.1%) and nine (52.9%) patients in groups A and B respectively were symptomatic for shorter than a year. Conclusion: The study had revealed that patients with increased signal intensities in preoperative T2 weighted cervical MRI images had significantly less recovery rates than the patients without any signal change in their preoperative T2 weighted cervical MRI images resulting in their decreased alleviation of symptoms and relatively unfavourable quality of life after surgery. Bang. J Neurosurgery 2025; 14(2): 112-117